2010
DOI: 10.1186/1471-2458-10-538
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of interventions to change six health behaviours: a review of reviews

Abstract: BackgroundSeveral World Health Organisation reports over recent years have highlighted the high incidence of chronic diseases such as diabetes, coronary heart disease and cancer. Contributory factors include unhealthy diets, alcohol and tobacco use and sedentary lifestyles. This paper reports the findings of a review of reviews of behavioural change interventions to reduce unhealthy behaviours or promote healthy behaviours. We included six different health-related behaviours in the review: healthy eating, phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
259
2
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(281 citation statements)
references
References 92 publications
7
259
2
13
Order By: Relevance
“…It is beyond the scope of this paper to discuss these in detail here, but reviews of the evidence [10] formed the basis of the National Institute for Health and Care Excellence (NICE) guidelines on approaches to health behavior change [11,12]. NICE is an independent organization, set up by the UK government in 1999 to help reduce variation in the availability and quality of NHS treatments and care.…”
Section: Et Al's Taxonomy Of 93mentioning
confidence: 99%
“…It is beyond the scope of this paper to discuss these in detail here, but reviews of the evidence [10] formed the basis of the National Institute for Health and Care Excellence (NICE) guidelines on approaches to health behavior change [11,12]. NICE is an independent organization, set up by the UK government in 1999 to help reduce variation in the availability and quality of NHS treatments and care.…”
Section: Et Al's Taxonomy Of 93mentioning
confidence: 99%
“…38 Risky behaviours related to lifestyle, always hard to change without suitable interventions, are usually established in childhood and often persist in adulthood. [39][40][41] Appropriate public health interventions should be implemented in China to reduce these risky behaviours and thereby lower the prevalence of the biological NCD risk factors to which they can lead, such as hypertension, raised blood glucose and hypercholesterolemia.…”
Section: Researchmentioning
confidence: 99%
“…One of the consequences of this research practice is maintaining the impression that gender is a homogenous category. Numerous studies have found significant gender differences in behaviour (9)(10), while a lower number analyse these differences within the gender (11). Our study focuses precisely on this aspect.…”
Section: Introductionmentioning
confidence: 93%